Contralateral Abdominal Pocketing in Salvation of Replanted Fingertips with Compromised Circulation. (14th October 2014) - Shim, Hyung-Sup; Kim, Dong-Hwi; Kwon, Ho; Jung, Sung-No
Abstract : Abdominal pocketing is one of the most useful methods in salvation of compromised replanted fingertips. Abdominal pocketing has generally been performed in the ipsilateral lower abdominal quadrant, but we have also performed contralateral pocketing at our institute. To determine which approach is more beneficial, a total of 40 patients underwent an abdominal pocketing procedure in either the ipsilateral or contralateral lower abdominal quadrant after fingertip replantation. Dates of abdominal pocketing after initial replantation, detachment after abdominal pocketing, range of motion (ROM) before abdominal pocketing, and sequential ROM after the detachment operation and date of full ROM recovery and Disabilities of Arm, Shoulder, and Hand questionnaire (DASH) score were recorded through medical chart review. Mean detachment date, mean abduction of shoulder after the detachment operation, and mean days to return to full ROM were not significantly different between the ipsilateral and contralateral pocketing groups. However, the mean DASH score was significantly lower in the contralateral group than the ipsilateral group. There were also fewer postoperative wound complications in the contralateral group than in the ipsilateral group. We, therefore, recommend contralateral abdominal pocketing rather than ipsilateral abdominal pocketing to increase patient comfort and reduce pain and complications.